2017
DOI: 10.1590/s1678-86212017000400183
|View full text |Cite
|
Sign up to set email alerts
|

Resilience skills used by front-line workers to assemble precast concrete structures: an exploratory study

Abstract: Abstractesides increasing productivity, prefabricated building systems can also contribute to the reduction of the levels of risk exposure by workers. However, there are several hazards that can be faced by workers involved in the assembly of prefabricated components, such as being struck by objects during lifting and handling of large components, and falls from height. This paper is focused on the assembly process of precast concrete building systems, widely used in Brazil. It is uses the Resilience Engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Furthermore, Li et al (2019) suggested that human motion models with the aid of vision-based applications can be used to identify unsafe behaviours due to inappropriate postures and body movements during job tasks. Although repetition and automation were found to have a positive effect on safety behaviour, occasionally it could result in negative safety incidents (Penaloza et al , 2017; Li et al , 2019). Therefore, it is essential to adjust these initiatives after a careful evaluation of job tasks of OSM.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Li et al (2019) suggested that human motion models with the aid of vision-based applications can be used to identify unsafe behaviours due to inappropriate postures and body movements during job tasks. Although repetition and automation were found to have a positive effect on safety behaviour, occasionally it could result in negative safety incidents (Penaloza et al , 2017; Li et al , 2019). Therefore, it is essential to adjust these initiatives after a careful evaluation of job tasks of OSM.…”
Section: Resultsmentioning
confidence: 99%
“…Source(s) Speedy [10]; [19]; [20]; [21]; [22] Cost effective [2]; [23]; [24]; [25]; [26]; [27] Highly Safe [28], [29], [30], [31], [32] Highly Productive [33]; [34]; [35] Environmentally Friendly [21]; [36]; [37]; [38]; [39]; [40] Speedy: Two Important benefits of the modularization method for construction are that several activities can be performed simultaneously [21], and weather conditions have little effect on the schedule [19]. As a result, the time required to complete a modular construction project is usually 40% less than that of traditional construction methods [19], which can be very important for projects with a need for a quick turnaround [41], such as such as post-disaster reconstruction of infrastructures, hospitals, etc.…”
Section: Advantagementioning
confidence: 99%
“…Several studies have investigated the effects of modularization on the safety of the laborers and revealed that it results in a significant decrease in the number of safety problems [30]. The rate of accidents occurring in construction projects reduces by 80% when the modular construction method is used [31]. Even though modularization usually decreases the rate of injuries at job sites, safety frameworks need to be established for this method as well [31].…”
Section: Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…RE has been applied to systems which involve high interdependence among the processes and high levels of uncertainty and variability (Perrow, 1984; Wehbe et al , 2016). Studies have been developed on construction projects in order to improve safety performance using RE concepts (Wehbe et al , 2016; Peñaloza et al , 2017).…”
Section: Introductionmentioning
confidence: 99%